Influence of patient-related characteristics on early migration in calcar-guided short-stem total hip arthroplasty: a 2-year migration analysis using EBRA-FCA. Issue 1 (December 2016) - Kutzner, Karl; Kovacevic, Mark; Freitag, Tobias; Fuchs, Andreas; Reichel, Heiko; Bieger, Ralf
Abstract Background Short stems have gained popularity in recent years. Because of encouraging clinical results, indications have been expended from young to elderly and obese patients. However, long-term results are lacking. The purpose of this study was to evaluate the influence of gender, age, body weight, body mass index (BMI), and offset version on short-stem migration in correlation to the clinical outcome. Methods The implant migration of 202 metaphyseal-anchoring, calcar-guided short stems in 151 patients was assessed by "Einzel-Bild-Roentgen-Analyse" femoral component analysis (EBRA-FCA, femoral component analysis) in a 2-year follow-up. Full weight bearing was allowed directly after surgery. Patients were divided into groups regarding gender, age, body weight, BMI, and offset version. The Harris hip score (HHS) and satisfaction on visual analogue scale (VAS) were analyzed. Results After 2 years, mean axial subsidence of all 202 implants was 1.43 mm (standard deviation, SD 1.45 mm). A continuous reduction of initially pronounced subsidence over time could be observed. None of the stems had to be revised. Statistically significant increased rates of subsidence were seen in male (1.68 mm; SD 1.56 mm;p  = 0.005) and heavy patients (1.54 mm; SD 1.48 mm;p  = 0.022). No differences in implant migration were found regarding age, BMI, and different offset versions. HHS improved markedly from 45.8 (SD 15.9) to 98.1 (SD 4.7) while satisfaction on VAS improved from 1.8 (SD 2.2) to 9.7 (SD 0.9) after 2 years. Conclusions The results suggest a migration pattern with initially pronounced subsidence followed by subsequent stabilization. Male and obese patients show a slightly increased initial subsidence without any signs of sustained micromovement. No correlation was found concerning clinical results and pronounced initial subsidence above the threshold of 1.5 mm. No aseptic loosening or other signs of implant failure were seen within the observation period of 2 years. Trial registration German Clinical Trials Register, DRKS00009834 .